Rediseño de las redes de distribución de aire acondicionado de buses de servicio público como estrategia de eficiencia energética y optimización del confort (2020)
In the transport industry, vehicle operating costs are an important issue to improve, in the same way thermal comfort for passenger inside a public transport bus (BRT) cabin represents a challenge, most likely in countries or cities with tropical climates such as Barranquilla. The main objective of this project is to propose several modifications that lead to the improvement of the user thermal comfort conditions inside the cabin by revising and proposing solutions that generate a better conditioned air distribution networks, reducing fuel consumption and making the system more attractive for the users. In order to achieve this goal three design alternatives are proposed: flow discretization through dampers on the ducts accionated by a control system, total redesign of the air conducts including linear diffusers and load regulation considering the bus occupation and on the other hand as a third alternative, a compendium of tower type fans are proposed all through the cabin aiming to increase air turbulence. The total redesign alternative is chosen, this consists in the sizing of flexible ducts together with a flow distribution depending on the occupation with the purpose of improving internal thermal comfort conditions which is verified by CFD simulations. Finally, taking current operating conditions as a baseline, improved and recommended parameters by ASHRAE are possible to visualize, thermal comfort in critical zones was improved, the mean temperature in the cabin decreased from 27°C to 23°C, the relative humidity went from 53,6% to 51,9%, while the mean air shot velocity has increased from 2,5 m/s to 5 m/s. It is recommended to perform deeper and more complex CFD simulations looking forward to optimize the design and location of air distributing system elements and associate this kind of studies with technologies and refrigeration devices modifications.